The Old English version of Bede's Historia ecclesiastica - Rowley, Sharon M. (Boydell & Brewer, 2011)
The first full-length study of the Old English version of Bede's masterwork, dealing with one of the most important texts to survive from Anglo-Saxon England. The subjects treated range from a detailed analysis of the manuscripts and the medieval use of them to a very satisfying conclusion that summarizes all the major issues related to the work, giving a compelling summary of the value and importance of this independent creation. Dr Rowley convincingly argues that the Old English version is not an inferior imitation of Bede's work, but represents an intelligent reworking of the text for a later generation. An exhaustive study and a major scholarly contribution.' GEORGE HARDIN BROWN, Professor of English emeritus, Stanford University. The Old English version of Bede's 'Historia ecclesiastica gentis anglorum' is one of the earliest and most substantial surviving works of Old English prose. Translated anonymously around the end of the ninth or beginning of the tenth century, the text, which is substantially shorter than Bede's original, was well known and actively used in medieval England, and was highly influential. However, despite its importance, it has been little studied. In this first book on the subject, the author places the work in its manuscript context, arguing that the text was an independent, ecclesiastical translation, thoughtfully revised for its new audience. Rather than looking back on the age of Bede from the perspective of a king centralizing power and building a community by recalling a glorious English past, the Old English version of Bede's 'Historia' transforms its source to focus on local history, key Anglo-Saxon saints, and their miracles. The author argues that its reading reflects an ecclesiastical setting more than a political one, with uses more hagiographical than royal; and that rather than being used as a class-book or crib, it functioned as a resource for vernacular preaching, as a corpus of vernacular saints' lives, for oral performance, and episcopal authority. Sharon M. Rowley is Associate Professor of English at Christopher Newport University.